Burger's medicinal chemistry, drug discovery and development / edited by Donald J. Abraham, David P. Rotella. - Abraham, Donald J., 1936-; Rotella, David P.; Burger, Alfred, 1905-2000. (Hoboken, N.J. : Wiley, 2010)
'Now in its seventh edition, Burger's Medicinal Chemistry, Drug Discovery and Development provides an established, recognized, authoritative and comprehensive source on medicinal chemistry and drug discovery and development. This flagship reference for medicinal chemists and pharmaceutical professions has been thoroughly updated and expanded across 8 volumes to incorporate the entire process of drug development (preclinical testing, clinical trials, etc.) alongside the traditional strengths in medicinal chemistry and drug discovery'--Provided by publisher.
v. 1. Methods in drug discovery -- v. 2. Discovering lead molecules -- v. 3. Drug development -- v. 4. Cardiovascular, endocrine, and metabolic disease -- v. 5. Pulmonary, bone, immunology, vitamins, and autocoid therapeutic agents -- v. 6. Cancer -- v. 7. Antiinfectives -- v. 8. CNS disorders.
Rev. ed. of: Burger's medicinal chemistry and drug discovery. 6th ed. / edited by Donald J. Abraham. 2003.
Keywords: Chemistry, Pharmaceutical -- methods; Biopharmaceutics -- methods; Drug Compounding -- methods